Pengaruh Model Pembelajaran Discovery Learning terhadap Peningkatan Keterampilan Proses Sains Peserta Didik Kelas VIII SMP Negeri 1 Bangkala - Al Ikhlas Dwi Ariyanto; Ramlawati Ramlawati (Universitas Negeri Makassar, 2022)
This study is a quasi-experimental research that aims to find out: 1) The improvement of science process skills of the students of class VIII SMPN 1 Bangkala which is taught by using the Discovery Learning model, 2) The improvement of science process skills of the students of class VIII SMPN 1 Bangkala which is taught by using the Direct Learning Model, and 3) the effect of the Discovery Learning model on improving science process skills of the students of class VIII SMPN 1 Bangkala. This type of research is a quasi-experimental research (Quasi-Experiment) and design of research is Nonequivalent Control Group Design with the population of all students of class VIII SMP Negeri 1 Bangkala consisting of 5 classes with a total of 140 students. The Sample selection by using purposive sampling as an experimental class of 23 students and a control class of 23 students. Descriptive analysis results on improving the science process skills of students obtained an average score of N-Gain in the experimental class 0.74 classified as high category and 0.63 in the control class classified as medium category. Based on the results of inferential analysis using t-test science process skills obtained = > = 1,68, at a significant level (α)= 0,05. Thus H0 rejected while H1 received and concluded that there is an influence of discovery learning model on improving science process skills of students of class VIII SMPN 1 Bangkala on the subject matter of usaha dan pesawat sederhana dalam kehidupan sehari-hari.